Analysis and Purification of Nkalagu (Nigeria) Limestone and Poultry Eggshells for the Production of Paint Grade Calcium Carbonate: Short Communication (Biological Sciences - PJSIR, 2005)
The local limestone (Nkalagu, Nigeria) and poultry eggshells were collected and analysed using gravimetric and spectrophotometric methods. The parameters determined were: moisture content, loss on ignition, impure silica, combined oxides     such as CaO, MgO, Fe O , Na O and K O. The carbonate contents fell short of that required (> 95%) for paint2    3          2                     2manufacture. The non-carbonate matters, regarded as impurities, were removed or reduced by chemical processes, which3 3 involved acid digestion through carbonation of the resultant filtrates. The purified CaCO grades from both these samples were compared with the commercially available grades. The purified grades showed improved whiting and fineness, indicating their usefulness for paints and other CaCO  applications.